Mode of allocation and social demographic factors correlate with impaired quality of life after liver transplantation. Issue 1 (December 2015) - Heits, Nils; Meer, Gunnar; Bernsmeier, Alexander; Guenther, Rainer; Malchow, Bjoern; Kuechler, Thomas; Becker, Thomas; Braun, Felix
Abstract Background Health-related Quality of life (HRQoL) is a major goal of clinical management after liver transplantation (LTx). There is still disagreement on the effects of social-demographic factors and changes in the allocation system on HRQoL. The aim of this study was to evaluate the impact of social-demographic factors, mode of organ-allocation, waiting time and hepatocellular carcinoma (HCC) on HRQoL after LTx. Methods HRQoL was assessed using the EORTC-QLQ-C30 questionnaire, which was sent to 238 recipients. Investigated parameters included age, sex, distance to transplant center, follow-up at hospital, size of hometown, highest education, marital status, having children, background liver disease, waiting time, mode of allocation, HCC, hospitalization after LTx and diagnosis of malignancy after LTx. All evaluated parameters were entered into multivariate linear regression analysis. Results Completed questionnaire were returned by 73 % of the recipients. After LTx, the HRQoL-function scales increased over time. Age, marital status, highest education, completed professional training, working status, job position, duration of waiting time to LTx, distance to transplant center, place offollow, HU-statuts, mode of organ allocation and duration of hospitalization were associated with significantly worse function- and significantly lower symptom scales. HCC as a primary disease did not affect HRQoL. Conclusions Low HRQoL correlated significantly with MELD-based organ allocation, more than 28-day hospitalization, divorced status, lower education- and non-working status, higher distance to transplant center, follow up at transplant center, HU-status, shorter waiting time to LTx and younger age. Improvement of HRQoL after LTx may require clinical management of pain, psychotherapy and financial support.